Commentary on the sentence of the Regional Court – July 26, 2013, ref. No. VI Ka 307/13 - Witczak, Karolina (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The article refers to the offence of fixation of the image of the naked person. The author tried to consider the issue of a possibility of image recognition when there was no information medium on which the image should be saved. In addition, the problem of significance of right to intimacy under art. 191a of the Penal Code was discussed. The act of playing of the image as a requirement to realize the feature of “fixation of the image” was also worth noting. Furthermore, the features of “violence” and “threat” were analyzed due to the type of resources used by the perpetrator to commit this offence. Finally, the matter of qualifying this act as an attempt to commit an offence was raised.